Profitability Ratio Analysis of Financial Performance at PT Kino Indonesia Tbk. On Indonesian Stock Exchange - Amor, Atika; Rauf, Abdul; Asrida, Asrida; Atsarina, Alyani (Rangkiang: Journal of Islamic Economics and Business, 2024)
This study aims to analyze the financial performance with a profitability ratio approach at PT Kino Indonesia Tbk. from 2020 to 2023. In this study, the type of research used was descriptive qualitative. The source of data in this study is documentation in the form of financial reports in the form of statement of financial position and income statements compiled by PT. Kino Indonesia Tbk. The data taken from IDX or www.idx.co.id. Based on the company's financial data management, the calculation uses the company's profitability ratios, including Gross Profit Margin, Net Profit Margin, Return On Asset,and Return On Equity. After reviewing it, it turns out that the average value of net profit margin, gross profit margin and return on equity is below the industry standard ratio. From this information it can be concluded that the company has not succeeded in increasing its financial percentage well, especially in 2022. In 2022 PT Kino Indonesia Tbk will experience quite large losses so that the GPM, NPM, ROA and ROE ratios will be far below those of similar industries.